2023
DOI: 10.3390/ma16041460
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Nanoparticles for Potential Antimicrobial Applications

Abstract: There is an increased interest in porous materials due to their unique properties such as high surface area, enhanced catalytic properties, and biological applications. Various solvent-based approaches have been already used to synthesize porous materials. However, the use of large volume of solvents, their toxicity, and time-consuming synthesis make this process less effective, at least in terms of principles of green chemistry. Mechanochemical synthesis is one of the effective eco-friendly alternatives to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 152 publications
0
16
0
Order By: Relevance
“…This technique offers several advantages including reduced pollution, cost-effectiveness, simple approach and handling. 326,327 These factors are critical in different industrial practices. In the early 20th century, W. Nernst categorized various branches of chemistry based on the energy source supplied to the system: electrochemistry, thermochemistry, and photochemistry.…”
Section: Green Corrosion Inhibition Using Energy-efficient Synthesismentioning
confidence: 99%
“…This technique offers several advantages including reduced pollution, cost-effectiveness, simple approach and handling. 326,327 These factors are critical in different industrial practices. In the early 20th century, W. Nernst categorized various branches of chemistry based on the energy source supplied to the system: electrochemistry, thermochemistry, and photochemistry.…”
Section: Green Corrosion Inhibition Using Energy-efficient Synthesismentioning
confidence: 99%
“…Research into the ball milling synthesis of ceramic oxide nanostructures has revealed several exciting possibilities. For instance, ball‐milled ceramic oxide nanostructures have shown promise in various applications, such as energy storage and conversion devices, catalysts, sensors, and biomedical applications 62,63 . The ability to tune their properties by manipulating their size, structure, and composition via ball milling offers an attractive approach to designing and optimizing these nanostructures for specific applications.…”
Section: Mechanism Of Mechanochemical Synthesis Of Nanostructured Oxi...mentioning
confidence: 99%
“…Nanomaterials are commercially accessible bulk materials in terms of electrical, magnetic, optical, catalytic, and medicinal properties (Khan et al, 2019). These characteristics may be related to the large surface area and quantum con nement effects per unit volume (Dubadi et al, 2023). Because of the simplicity of their production and promising physicochemical features, Nickel oxide nanoparticles (NiO-NPs) have several advantages (Barzinjy et al, 2020;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The development of NPs from plants is one of the acceptable, straightforward, and green ways to generate NPs (Dubadi et al, 2023;Khan et al, 2021;Srihasam et al, 2020). The Punicaceae family includes pomegranate (Punica granatum L.), a crucial source of polyphenols, avonoids, and rich natural antioxidants (El-Beltagi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%